Wilkins-Hearst Antarctic Expedition 1928-1929 map of the Antarctic compiled by the American Geographical Society of New York (American Geographical Society of New York, 1929)
Relief shown by spot heights. Depth shown by isolines and spot heights.; Includes ancillary map "Map of the Antarctic Archipelago, scale 1:2,500,000," and b&w ill. Color; 1:12,500,000